Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21608/zjar.2019.51906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral, Organic and Bio Fertilization on Wheat Production in Two Different Soils

Abstract: Biological experiment was conducted in the clay and sandy soils to study the effect of inorganic, organic and bio fertilization on growth and yield components as well as N, P and Kuptake by wheat plants. Ammonium sulphate (N) was added at the rates of 25 [50% the recommended dose (RD)] and 50 (100% RD) mg N kg-1 soil, while ordinary superphosphate (P 1) and rock phosphate (P 2) were applied at the rates of 9.72 (50% RD) and 19.44 (100% RD mg P kg-1 soil. Potassium sulphate (K 1) and feldspar (K 2) were added a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…Application of amino acids has a beneficial effect on the production of other compounds such as amines, purines, alkaloids, pyrimidines, enzymes, vitamins and terpenoids, enhancing photosynthesis and thus increasing grain yield [15]. Mohamed [57] reported that the application of an extract of amino acids and yeast produced a beneficial effect on the reproductive development of plants, which also affected grain yield. It was noted that by foliar application of amino acids and yeast during drought, higher numbers of spikes and grains could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Application of amino acids has a beneficial effect on the production of other compounds such as amines, purines, alkaloids, pyrimidines, enzymes, vitamins and terpenoids, enhancing photosynthesis and thus increasing grain yield [15]. Mohamed [57] reported that the application of an extract of amino acids and yeast produced a beneficial effect on the reproductive development of plants, which also affected grain yield. It was noted that by foliar application of amino acids and yeast during drought, higher numbers of spikes and grains could be obtained.…”
Section: Discussionmentioning
confidence: 99%